2010
DOI: 10.1002/jcb.22729
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of TNF‐α‐induced migration and hepatocyte growth factor production in human mesenchymal stem cells

Abstract: Accumulating evidence suggests that mesenchymal stem cells (MSCs) may decrease destructive inflammation and reduce tissue loss. Tumor necrosis factor-α (TNF-α) plays a central role in induction of proinflammatory signaling and paradoxically activates intracellular anti-inflammatory survival pathways. In this study, we investigated whether TNF-α could induce a chemotactic effect on human MSCs and stimulate their production of anti-inflammatory factors in vitro, as well as determined mechanisms that mediated thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
5
36
1
Order By: Relevance
“…Functionally, the C-domain of heparanase can mediate enhanced Akt phosphorylation (35). Interestingly, it was recently demonstrated that induction of Akt phosphorylation leads to enhanced HGF expression and secretion in human mesenchymal stem cells (36). However, heparanase did not alter levels of Akt phosphorylation in the myeloma cells studied here 4 indicating that the C-domain likely has functions that have not yet been uncovered.…”
Section: Discussionmentioning
confidence: 81%
“…Functionally, the C-domain of heparanase can mediate enhanced Akt phosphorylation (35). Interestingly, it was recently demonstrated that induction of Akt phosphorylation leads to enhanced HGF expression and secretion in human mesenchymal stem cells (36). However, heparanase did not alter levels of Akt phosphorylation in the myeloma cells studied here 4 indicating that the C-domain likely has functions that have not yet been uncovered.…”
Section: Discussionmentioning
confidence: 81%
“…MSC accumulation was significantly decreased through parthenolide inhibition of NF-kB activity. Although several studies have shown that mitogen-activated protein kinase (MAPK) phosphorylation by growth factors are involved in MSC migration (16,17), parthenolide did not inhibit MAPK phosphorylation (data not shown). Therefore, at least parthenolide treatment did not affect in migration ability of MSCs toward growth factors from tumors in this experimental settings.…”
Section: Discussionmentioning
confidence: 88%
“…The factors that lead to up-regulation of HGF expression in the setting of bleomycin-induced lung injury are beyond the scope of this project, but a variety of proteases and inflammatory cytokines, such as interleukin (IL)-6, IL-1a, IL-1b and TNF-a, have been shown to increase HGF mRNA and protein expression [26][27][28][29][30]. Other data [7] provide an additional variable in persistent HGF production that involves previous exposure to endogenous apoptotic cells or cell debris in lung injury lesions since the phagocytic indexes in BAL alveolar macrophages increased following bacterial infections.…”
Section: Discussionmentioning
confidence: 99%